2021
DOI: 10.1200/po.21.00281
|View full text |Cite
|
Sign up to set email alerts
|

Germline Sequencing Improves Tumor-Only Sequencing Interpretation in a Precision Genomic Study of Patients With Pediatric Solid Tumor

Abstract: PURPOSE Molecular tumor profiling is becoming a routine part of clinical cancer care, typically involving tumor-only panel testing without matched germline. We hypothesized that integrated germline sequencing could improve clinical interpretation and enhance the identification of germline variants with significant hereditary risks. MATERIALS AND METHODS Tumors from pediatric patients with high-risk, extracranial solid malignancies were sequenced with a targeted panel of cancer-associated genes. Later, germline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…[15][16][17] Studies reporting on germline P/LP variants in RMS (without clarifying FOXO1 fusion status) are presented in Table 1. 11,13,[15][16][17][18][19][20][21][22] In these studies, P/LP germline variants were most frequently detected in TP53, neurofibromatosis type 1 (NF1), and DICER1, which is consistent with the classic CPSs known to predispose to RMS: NF1, Li-Fraumeni syndrome (LFS), DICER1 syndrome, as well as Beckwith-Wiedemann syndrome (BWS) and Costello syndrome. Young age of RMS onset (≀3 years), as well as specific tumor locations (e.g., cervical/ovary) and presence of anaplasia are indicators that there may be an underlying CPS.…”
Section: Patients With Rms P/lp Germline Variant (%) Details Of Germl...supporting
confidence: 70%
“…[15][16][17] Studies reporting on germline P/LP variants in RMS (without clarifying FOXO1 fusion status) are presented in Table 1. 11,13,[15][16][17][18][19][20][21][22] In these studies, P/LP germline variants were most frequently detected in TP53, neurofibromatosis type 1 (NF1), and DICER1, which is consistent with the classic CPSs known to predispose to RMS: NF1, Li-Fraumeni syndrome (LFS), DICER1 syndrome, as well as Beckwith-Wiedemann syndrome (BWS) and Costello syndrome. Young age of RMS onset (≀3 years), as well as specific tumor locations (e.g., cervical/ovary) and presence of anaplasia are indicators that there may be an underlying CPS.…”
Section: Patients With Rms P/lp Germline Variant (%) Details Of Germl...supporting
confidence: 70%
“…Additionally, there must be a careful selection when deciding how to discriminate somatic from germline variants. However, tumor-only sequencing has the advantage of being cost-effective, helping inform a diagnostic, predict prognosis for certain tumors, and providing tumor profiling for mutational burden [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have described the benefits of matched paired tumor‐normal sequencing tests, which include the reduction of the number of germline variants that often are filtered out in somatic sequencing depending on their population frequency or some computational filters that may also mask germline variants associated with cancer predisposition genes, allowing improvement of the accuracy of variant reporting to refine diagnoses, aid in a treatment decisions, and refer patients and families to genetic counseling when indicated. Schienda and collaborators showed how the integration of germline sequencing with molecular tumor profiling in a subset of children with solid malignancies enrolled in the Genomic Assessment Improves Novel Therapy (GAIN) consortium (Clinical Trials ID: NCT02520713) could improve clinical interpretation and enhance the identification of germline variants with significant hereditary risks (Schienda et al., 2021). They found that 66% of SNVs identified in the tumors were reported as pathogenic, likely‐pathogenic or variants of uncertain significance in germline sequencing and only 29% of them were present solely in the tumor sequencing data, and thus determined to be of somatic origin.…”
Section: Cancer Predisposition On the Basis Of Genomic Findings Withi...mentioning
confidence: 99%